A Note on Inflation and Concentration - Gisser, Micha; Johnson, Ronald N. (Journal of Political Economy, 1979)
The view that the inflationary process experienced in the United States over the last 10 years can be largely attributed to increasing concentration in the private sector has once again regained a degree of prominence. We offer calculations showing the effect of increasing concentration in the consumer price index. The results indicate that the act of reducing concentration, if successful is likely to have little impact on the consumer price index.